“All Tables Were to be Made Round”. The Circumstances of the Negotiations About the Marriage of Teresa Kunegunda Sobieska in the Light of the Kazimierz Sarneckis’ Messages - Skrzypietz, Aleksandra (Verba volant, scripta manent: Księga jubileuszowa dedykowana Profesorowi Zbigniewowi Anusikowi w sześćdziesiątą piątą rocznicę urodzin, 2022)
The article aims to present the circumstances of the negotiations about the marriage of Princess Teresa Kunegunda Sobieska. Thanks to the messages from the court, it is known what the preparations for receiving the Bavarian envoy at the court looked like and who was appointed to negotiate on behalf of Jan III. The sources also show the difficulties that arose during these talks and the doubts of both parties. It should be emphasized that thanks to the dedication of both parties the marriage contract was signed swiftly, within less than a month. The preserved sources allow us to see this time at court with all its particularities. There were long discussions between the royal couple, their closest advisers, a commission appointed to negotiate with the envoy, and numerous entertainment to show the princess, her family, and the royal court itself in all their splendour.